The Impact of STAD on Arabic Learning Outcomes of Tenth Grade In Senior High School Student - Fitria, Wira; Zulheddi, Zulheddi (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2025)
The Arabic language learning at MAN 4 Medan indicates that some students exhibit a lack of enthusiasm, limited interaction, and ineffective collaboration among students. Additionally, teachers face challenges such as time and resource constraints, which result in low student learning outcomes. This research aims to identify the implementation of the STAD (Student Teams Achievement Divisions) cooperative learning strategy in Arabic language instruction and to evaluate its impact on student learning outcomes. The study involved 30 students from grade tenth of MAN 4 Medan as samples. Research instruments included Pre and Post Tests, observation sheets, and student response questionnaires. The results show a significant improvement in student learning outcomes, with the average post-test score (82.8%) being higher than the pre-test score (53.5%). N-Gain analysis indicates a moderate increase in learning effectiveness (0.6). Thus, the STAD strategy has proven effective in enhancing Arabic language learning outcomes and can serve as an alternative in Arabic language teaching in schools.